Pengaruh Media Visual Powerpoint Terhadap Hasil Belajar Seni Budaya (Tari) Di Kelas VIII-2 SMP Negeri 12 Lubuk Linggau Provinsi Sumatera Selatan - Putri Puja Hasanah; Susmiarti Susmiarti (SENDRATASIK UNP, 2021)
This research aims to explain the significant influence or not on the use of audiovisual powerpoint media on the results of studying Cultural Arts (Dance) in Grade VIII-2 SMP Negeri 12 Lubuklinggau South Sumatra Province. The design of the study used was a simple experimental study with one sample on 36 students of grade VIII-2 SMP Negeri 12 Lubuklinggau. The design of this one case one sample study will place students at once as control objects and research objects. Research instruments are data on student learning results obtained from post-test 1 and 2 after KBM. The results of the study prove that the hypothesis of research work is accepted, where there is a significant influence on the use of visual media powerpoint on the results of learning cultural arts (dance) in Grade VIII-2 SMP Negeri 12 Lubuklinggau South Sumatra Province. These results also explain that the use of more creative and interactive powerpoint media, where videos are included in the powerpoint media encourages better student attention. With good attention in learning, resulting in enthusiastic and interested students in learning dance. As a result of enthusiasm, attention and interest in learning the dance, the results of students' learning can be improved.